Constrained Physical Design Tuning - Chaudhuri, Surajit; Bruno, Nicolas (Proceedings of the International Conference on Very Large Databases (VLDB), 2008)
Existing solutions to the automated physical design problem in database systems attempt tominimize execution costs of input workloads for a given a storage constraint. In this paper, we argue that this model is not flexible enough to address several real-world situations. To overcome this limitation, we introduce a constraint language that is simple yet powerful enough to express many important scenarios. We build upon an existing transformation-based framework to effectively incorporate constraints in the search space. We then show experimentally that we are able to handle a rich class of constraints and that our proposed technique scales gracefully.